Ethics, computing, and medicine : informatics and the transformation of health care - Goodman, Kenneth W., 1954- (Cambridge University Press, 1998)
New technology always raises compelling ethical questions. As those in medicine increasingly depend on computers and other intelligent machines, the intersection of ethics, computing and the health professions grows much more complex and significant. This book attempts systematically to identify and address the full range of ethical issues that arise when intelligent machines are used in medicine, nursing, psychology, and allied health professions. It maps and explores a variety of important issues and controversies, including ethics and evaluation in computational medicine, patient and provider confidentiality, responsibility for use of computers in medicine, appropriate use of decision support systems, outcomes of research and computational prognosis (including mortality predictions), and computer-based biomedical research - especially meta-analysis. This book is accessible to participants in the fields of bioethics and medical informatics. It is appropriate for physicians, nurses, administrators, ethicists, health attorneys, advanced undergraduates and graduate students.
Keywords: Medicine -- Data processing -- Moral and ethical aspects.; Medical records.; Risk.; Managed care plans (Medical care); Confidential communications.; Economics.; Medical care.; Probabilities.; Social values.; Bioethics.; Decision making.; Evidence-based medicine.; Informed consent (Medical law); Physician and patient.; Risk assessment.; Computer networks.; Telecommunication in medicine.; Information services.; Vocational qualifications.; Philosophy.; Thought and thinking.; Medical personnel and patient.; National health services.; Social psychology.; Health services accessibility.; Social control.; Medical personnel.; Computer systems.; Humanities.; Forensic psychiatry.; Prognosis.; Communication.; Risk management.; Clinical medicine.; Health services administration.; Social sciences.; Statistics.; Weights and measures.; Telecommunication.; Health planning.; Therapeutics.; Human rights.; Social groups.; Human information processing.; Human behavior.; Sociology.; Information storage and retrieval systems.; Public health.; Diagnosis.; Mass media.; Misinformation.; Statistics -- Methodology.; Health Care Rationing; Medical Futility; Medical Informatics; Medical Records; Risk; Managed Care Programs; Withholding Treatment; Confidentiality; Economics; Patient Care; Probability; Social Values; Bioethics; Decision Making; Delivery of Health Care; Ethics; Evidence-Based Medicine; Informed Consent; Physician-Patient Relations; Risk Assessment; Uncertainty; Computer Communication Networks; Databases, Factual; Information Dissemination; Quality of Health Care; Telemedicine; Information Services; Professional Autonomy; Professional Competence; Computers; Jurisprudence; Social Responsibility; Reference Standards; Resource Allocation; Professional Role; Medicine; Philosophy; Thinking; Patient Rights; Professional-Patient Relations; Health Services; Mathematical Concepts; Psychology, Social; Epidemiologic Measurements; Health Services Accessibility; Social Control, Formal; Health Occupations; Computer Systems